THE STRATEGIES TO OVERCOME LAZINESS IN LEARNING SOCIAL STUDIES IN UNIVERSITY - Mahfudz Sulaiman (Universitas Islam Zainul Hasan Genggong, 2024)
This discussion focuses on social studies education at the tertiary level, with an emphasis on challenges and strategies to overcome laziness in learning. The study used a descriptive qualitative approach with a case study at the college. The research involved two lecturers as well as 30 students from the college. The results showed variations in students' interest and engagement with social studies subjects, with some students showing high interest, while others were less interested. The lecturers used various strategies to increase students' interest, such as relating the material to everyday life, using learning media such as videos and interactive technology, and involving students in practical activities such as group projects. The findings also show that many students feel bored and lazy with monotonous and less interactive teaching methods, so they tend to lose interest in learning. The implication of this study is the need to continuously innovate in teaching approaches to maintain students' interest and maximize the potential of social studies learning at the tertiary level.